Análisis del estado de conservación de anfibios en zonas con diferentes niveles de disturbio en la provincia de Pichincha - Salazar Naranjo, Daniel Alejandro (2018)
Amphibian populations are affected mainly by climate change and the fragmentation of hábitat, the same which are originated from human form. For this reason it was know the distribution of the different species of amphibians, catalougued as: VULNERABLE, IN DANGER AND CRITICALLY ENDANGERED in the province of Pichincha where it was stablish priority areas for the conservation of amphibians. This was realize a retrospective method for obtaining information of the distribution of the amphibians within the province of Pichincha, found at AmphibiaWeb Ecuador with a total of 995 records. In addition to required information on projects in implementation of the GAD of Pichincha; It was classified according to their level of disturbance in low medium and high. Together with the use of a software of onformation systems geographic five priority conservation areas are established, these are two high priority areas located in the parishes of Manuel Cornejo Astorga (Tandapi) and Nanegal whit an extensión of 2580,53 ha and 762,77 ha respectively and three medium priority areas located in the parishes of Manuel Cornejo Astorga (Tandapi), Lloa and Mindo with an extensión of 4514,80 ha, 9704,55 ha and 4480,44 ha respectively according to the matrix for the analysis of the priority conservation areas. Within the priority areas of conservation are located six species of amphibians, these are: Eleutherodactylus crenunguis, Eleutherodactylus mindo, Eleutherodactylus rosadoi, Hyloxalus awa, Atelopus mindoensis y Atelopus longirostris; the latter listed critically endangered by AmphibiaWeb Ecuador.